Innovation Through AI Integration: A Study of AI Technology Adoption for the Maritime Inspection and Consulting Sector using Soft System Methodology - Suprajeni, M. Raihan; Yopan, Muhamad; Fitriati, Rachma (Manunggal Halim Jaya, 2025)
The maritime industry, a global powerhouse for trade and transportation, is on the cusp of a transformative era driven by Artificial Intelligence (AI). This paper explores the potential of AI to revolutionize various aspects of the maritime sector, from navigation and route optimization to predictive maintenance and enhanced safety. This paper will study AI implementation in the inspection and consulting industry. This AI will help speed up the maritime industry's regulatory compliance process and maintenance services. The study showed four main stakeholders in AI implementation: Operational experts, managers, clients, and the AI team. Each stakeholder has a crucial role in successfully implementing AI in this industry. This study will map out each stakeholder's interest using SSM, giving a clear picture of what each stakeholder wants and their apprehensions. The result of this study is some conditions that need to be met by each stakeholder for the implementation of AI in this sector to be successful.